Exploring The Impact of Traditional Media on Social Empowerment in Rural India: A Developmental Perspective With Special Reference To Rural Areas Of Meerut Region - Tomer, Harsh; Sharma, Gunjan (Journal of Neonatal Surgery, 2025)
Aim:The research examines how exposure to traditional media affects social empowerment in rural communities of Meerut region Uttar Pradesh India using six measurement dimensions about frequency, type, content relevance, accessibility, credibility and cultural appropriateness. Methodology:A quantitative cross-sectional study included the administration of structured surveys to 415 rural participants who became part of the sample through purposive sampling. This study used Media Dependency Theory together with Empowerment Theory to evaluate awareness levels alongside community engagement and self-efficacy and mobility and gender equality perception and civic engagement as empowerment outcomes. Statistical Methods:The researchers conducted their analysis through SPSS utilizing descriptive statistics and reliability tests (Cronbach’s alpha) with normality testing (Shapiro–Wilk) and Pearson correlation and multiple linear regression. Results:Traditional media exposure dimensions showed positive relationships with social empowerment and credibility and trust achieved the highest correlation rates (β = 0.235) followed by content relevance (β = 0.214) and exposure frequency (β = 0.211) at p < 0.01. Social empowerment received 42% total explanation from the regression model which produced an adjusted R value of 0.411. Originality/Value:Empirical findings about traditional media and their impact on rural empowerment now exist through research in areas which experience low levels of digital access. The proposed multidimensional measurement method of media exposure shows culturally appropriate and reliable media continues to be a strong mechanism for rural Indian communities to thrive in participatory development.